The relevance of manganese in the ocean for the climatic cycles in the quaternary: Vorgelegt in der Sitzung vom 18. November 1989 - Mangini, Augusto; Eisenhauer, Anton; Walter, Peter (Sitzungsberichte der Heidelberger Akademie der Wissenschaften, Mathematisch-naturwissenschaftliche Klasse Jahrgang 1990, 4. Abhandlung, 1990)
The model presented here provides an explanation of the rapid response of atmospheric CO2 to increasing solar insolation. The surprising conclusion is that the oceanic (redox-)cycle of a minor element may have had a major impact on Earth's climate